The Implementation of Self-Directed Dialogue to Improve Students’ Speaking Ability - Melia Nova; Syarifudin Syarifudin; Soni Ariawan (International Journal of English and Applied Linguistics (IJEAL), 2022)
The purpose of this study was to find out the improvement of students speaking ability through the implementation of the self-directed dialogue technique, and student activities when the Self-directed Dialogue was applied to English subjects in the first grade of MA Darussalam, Beremi for the 2021/2022 academic year. In this study, the researcher used classroom action research as a research design by employing observation, tests, and documentation as techniques to gain the data. Observations were made to determine the application of self-directed dialogue techniques during the teaching and learning process while tests were used to measure student achievement in speaking ability. The subjects of this study were students in first grade of MA Darussalam Bermi with 21 students in the class. Researchers used qualitative and quantitative data analysis in calculating and analyzing data. The results of this study indicate that the self-directed dialogue technique can improve students' speaking ability. This can be seen from the results of a significant increase in each cycle. The score before implementing the technique was 48, the result of post-test 1 was 74.43, and post-test 2 was 84.43. This means that the students' speaking ability increases after applying the self-directed dialogue technique in the first grade of MA Darussalam Bermi in the 2021/2022 academic year.